Impact of ascending aortic prosthetic grafts on early postoperative descending aortic biomechanics on cardiac magnetic resonance imaging. (29th November 2021) - Palumbo, Maria C; Redaelli, Alberto; Wingo, Matthew; Tak, Katherine A; Leonard, Jeremy R; Kim, Jiwon; Rong, Lisa Q; Park, Christine; Mitlak, Hannah W; Devereux, Richard B; Roman, Mary J; RoyChoudury, Arindam; et al.
Abstract: OBJECTIVES: Among patients with ascending thoracic aortic aneurysms, prosthetic graft replacement yields major benefits but risk for recurrent aortic events persists for which mechanism is poorly understood. This pilot study employed cardiac magnetic resonance to test the impact of proximal prosthetic grafts on downstream aortic flow and vascular biomechanics. METHODS: Cardiac magnetic resonance imaging was prospectively performed in patients with thoracic aortic aneurysms undergoing surgical (Dacron) prosthetic graft implantation. Imaging included time resolved (4-dimensional) phase velocity encoded cardiac magnetic resonance for flow quantification and cine-cardiac magnetic resonance for aortic wall distensibility/strain. RESULTS: Twenty-nine patients with thoracic aortic aneurysms undergoing proximal aortic graft replacement were studied; cardiac magnetic resonance was performed pre- [12 (4, 21) days] and postoperatively [6.4 (6.2, 7.2) months]. Postoperatively, flow velocity and wall shear stress increased in the arch and descending aorta ( P  < 0.05); increases were greatest in hereditary aneurysm patients. Global circumferential strain correlated with wall shear stress ( r  = 0.60–0.72, P  < 0.001); strain increased postoperatively in the native descending and thoraco-abdominal aorta ( P  < 0.001). Graft-induced changes in biomechanical properties of the distal native ascending aorta were associated with post-surgical changes in descending aortic wall shear stress, as evidenced by correlations ( r = −0.39–0.52; P  ≤ 0.05) between graft-induced reduction of ascending aortic distensibility and increased distal native aortic wall shear stress following grafting. CONCLUSIONS: Prosthetic graft replacement of the ascending aorta increases downstream aortic wall shear stress and strain. Postoperative increments in descending aortic wall shear stress correlate with reduced ascending aortic distensibility, suggesting that grafts provide a nidus for high energy flow and adverse distal aortic remodelling. Abstract : Prosthetic aortic graft replacement is widely used to treat patients with thoracic aortic aneurysms (TAAs).